Anion exchange membranes with high power density and energy efficiency for aqueous organic redox flow batteries. (10th January 2023) - Tsehaye, Misgina Tilahun; Yang, Xian; Janoschka, Tobias; Hager, Martin D.; Schubert, Ulrich S.; Planes, Emilie; Alloin, Fannie; Iojoiu, Cristina
Abstract: Membrane development in organic redox flow batteries (ORFBs) is of significant importance. Herein, we designed a series of anion exchange membranes made from poly( p -phenylene oxide) (PPO) with different degrees of functionalization, cationic moieties and crosslinking degrees. We tested them in a N, N, N -2, 2, 6, 6-heptamethylpiperidinyl oxy-4-ammonium chloride/1, 1′-dimethyl-4, 4′-bipyridinium dichloride (TMA-TEMPO/MV) based ORFB single cell to investigate the structure-property-performance relationship. The common problem of active species crossover is solved by controlling the membrane water uptake below 70 wt.%, resulting in stable systems with coulombic efficiency of over 99.3%. The cell employing a membrane prepared from PPO and trimethylamine moiety attached via a C6-spacer achieved the best overall cell performance. It delivered high capacity retention (94% after over 100 consecutive cycles) and higher peak power density (293 mW·cm −2 at 16 mL·min −1 ) and energy efficiency (80%) than the commercial reference memane FAA-3-50. Graphical abstract: By controlling the water uptake below 70 wt.% and involving a C6 spacer, the obtained membranes maintain excellent ion selectivity and conductivity, resulting in enhanced battery performance that breaks through the commercial membrane. Image, graphical abstract